Folate-targeted intraoperative fluorescence, OTL38, in robotic-assisted laparoscopic partial nephrectomy. (4th July 2021) - Sulek, Jay E.; Steward, James E.; Bahler, Clinton D.; Jacobsen, Max H.; Sundaram, Amitha; Shum, Cheuk Fan; Sandusky, George E.; Low, Philip S.; Sundaram, Chandru P.
Abstract: Objective: To investigate the safety and efficacy of OTL38, a folate-targeted, intraoperative fluorescence agent, in patients undergoing robotic-assisted laparoscopic partial nephrectomy. Methods: Patients with proven or suspected localized renal cell carcinoma at a single academic institution were selected from 2016 to 2018. Patients received one dose of OTL38 at 0.025 mg/kg prior to robotic-assisted laparoscopic partial nephrectomy. The da Vinci Fluorescence Imaging Vision System was used to identify the tumor and inspect for residual disease after resection. Immunohistochemistry was performed to quantify folate receptor alpha in both the tumor and surrounding normal parenchyma. Patient follow-up was 1 month. Outcome data included descriptive statistics of the patient cohort and surgeon and pathologist surveys. Results: Ten cases were performed. Mean patient age was 62.9 years (range = 50–70). Mean tumor size was 2.45 cm. Pathologic tumor stages ranged from T1a–T3a. Histologic tumor types included clear cell, chromophobe, type 1 papillary renal cell carcinoma and oncocytoma. The tumors did not fluoresce, while the surrounding normal parenchyma did show fluorescence. No adverse reactions were seen. Staining for folate receptor alpha was localized to the proximal renal tubules. Average staining in normal surrounding renal parenchyma was significantly greater than staining observed in tumor tissue (0.2086 vs 0.0467; p  = 0.002). The mean difference in staining between tumor tissue and surrounding normal renal parenchyma was 0.1619 (95% CI = 0.0796–0.2442). Conclusions: Based on our initial experience, OTL38 shows potential as a safe, effective and easy to use tool to improve visualization and resection of renal tumors.